Novel Androgen Receptor Inhibitors in Non-Metastatic, Castration-Resistant Prostate Cancer: A Systematic Review and Network Meta-Analysis - Mulati, Yelin; Fan, Yu; Yu, Wei; Zhang, Qian; He, Zhisong (Frontiers in Oncology, 2021)
Introduction：Enzalutamide, apalutamide and darolutamide have all been approved by FDA to treat high-risk nonmetastatic castration-resistant prostate cancer (nmCRPC) since 2018 based on interim results of several phase III clinical trails. Final analysis of long-term overall survival (OS) and adverse events (AEs) results of these trials have been successively published recently. To help clinical practice to precisely select optimal treatment for high-risk nmCRPC patients, we performed a network meta-analysis to indirectly compare the final long-term results among these medications. Methods：PubMed, EMBASE and Cochrane Libraries were searched for phase III clinical trail that reports OS and AEs results in nmCRPC patients published before January 30, 2021. Primary outcome was OS, secondary outcomes were Time to first chemotherapy, Subsequent antineoplastic therapy rate, and AEs. Firstly, class-level effect was assessed as the second-generation androgen receptor antagonists (SGARAs) were regarded as one whole class compared with placebo through traditional meta-analysis by using Revman 5.4, then a Bayesian network meta-analysis was conducted to give indirect comparison among SGARAs by using R 3.5.3 software. Subgroup analysis of OS was only conducted in the certain subgroups which were available in all included studies. Results：Three eligible studies including 4104 participants were finally selected. OS was significantly improved by the SGARAs as a class compared with placebo (HR, 0.74; 95%CI, 0.66-0.84). Darolutamide had the highest likelihood of providing best OS (p-score=0.802). SGARAs also significantly delayed the first time to chemotherapy (HR, 0.58；95％CI, 0.50-0.66). When compared with darolutamide, enzalutamide caused significantly higher toxicity in terms of any AEs (OR, 2.3； 95％CI,1.5-3.7) and AEs of grade 3 or higher (OR, 1.6; 95%CI, 1.1-2.2), apalutamide caused significantly more AEs of grade 3 or higher (OR, 1.9; 95%CI, 1.4-2.7) and serious AEs (OR, 1.9; 95％CI, 1.3-2.8). Subgroup analysis showed that SGARAs as a group significantly improved OS in ECOG=1 population, although insignificant results were found in these patients from included studies. Conclusions：SGARAs combined with ADT significantly improved OS when compared with ADT alone in high-risk nmCRPC patients. Darolutamide may not only provide best OS, but also have the most favorable safety profile among the included SGARAs for high-risk nmCRPC patients.